Intense Sweetness Surpasses Cocaine Reward - Lenoir, Magalie; Serre, Fuschia; Cantin, Lauriane; Ahmed, Serge H. (PLOS ONE, 2007)
BackgroundRefined sugars (e.g., sucrose, fructose) were absent in the diet of most people until very recently in human history. Today overconsumption of diets rich in sugars contributes together with other factors to drive the current obesity epidemic. Overconsumption of sugar-dense foods or beverages is initially motivated by the pleasure of sweet taste and is often compared to drug addiction. Though there are many biological commonalities between sweetened diets and drugs of abuse, the addictive potential of the former relative to the latter is currently unknown.Methodology/Principal findingsHere we report that when rats were allowed to choose mutually-exclusively between water sweetened with saccharin–an intense calorie-free sweetener–and intravenous cocaine–a highly addictive and harmful substance–the large majority of animals (94%) preferred the sweet taste of saccharin. The preference for saccharin was not attributable to its unnatural ability to induce sweetness without calories because the same preference was also observed with sucrose, a natural sugar. Finally, the preference for saccharin was not surmountable by increasing doses of cocaine and was observed despite either cocaine intoxication, sensitization or intake escalation–the latter being a hallmark of drug addiction.ConclusionsOur findings clearly demonstrate that intense sweetness can surpass cocaine reward, even in drug-sensitized and -addicted individuals. We speculate that the addictive potential of intense sweetness results from an inborn hypersensitivity to sweet tastants. In most mammals, including rats and humans, sweet receptors evolved in ancestral environments poor in sugars and are thus not adapted to high concentrations of sweet tastants. The supranormal stimulation of these receptors by sugar-rich diets, such as those now widely available in modern societies, would generate a supranormal reward signal in the brain, with the potential to override self-control mechanisms and thus to lead to addiction.